Genetic variability in SQSTM1 and risk of early-onset Alzheimer dementia: a European early-onset dementia consortium study - Cuyvers, Elise; van der Zee, Julie; Bettens, Karolien; Engelborghs, Sebastiaan; Vandenbulcke, Mathieu; Robberecht, Caroline; Dillen, Lubina; Merlin, Céline; Geerts, Nathalie; Graff, Caroline; Thonberg, Håkan; Chiang, Huei-Hsin; et al. (Neurobiology of aging, 2015)
Meta-analysis of existing genome-wide association studies on Alzheimer's disease (AD) showed subgenome-wide association of an intronic variant in the sequestosome 1 (SQSTM1) gene with AD. We performed targeted resequencing of SQSTM1 in Flanders-Belgian AD patients selected to be enriched for a genetic background (n = 435) and geographically matched nonaffected individuals (n = 872) to investigate the role of both common and rare SQSTM1 variants. Results were extended to the European early-onset dementia cohorts (926 early-onset Alzheimer's disease [EOAD] patients and 1476 nonaffected individuals). Of the 61 detected exonic variants in SQSTM1, the majority were rare (n = 57). Rare variant (minor allele frequency <0.01) burden analysis did not reveal an increased frequency of rare variants in EOAD patients in any of the separate study populations nor when meta-analyzing all cohorts. Common variants p.D292= and p.R312= showed nominal association with AD (odds ratiop.D292= = 1.11 [95% confidence interval = 1-1.22], p = 0.04), only when including the Flanders-Belgian cohort in the meta-analysis. We cannot exclude a role of SQSTM1 genetic variability in late-onset AD, but our data indicate that SQSTM1 does not play a major role in the etiology of EOAD.
Keywords: Adaptor Proteins, Signal Transducing; Meta-Analysis as Topic; Male; kohortové studie; Belgium; genetická variace; Cohort Studies; sekvestosom 1; European early-onset dementia consortium; Sequence Analysis, DNA; sekvenční analýza DNA; metaanalýza jako téma; Alzheimerova nemoc; Alzheimer Disease; Aged; mužské pohlaví; senioři; Alzheimer's disease; Sequestosome-1 Protein; lidé; ženské pohlaví; Humans; Meta-analysis; Belgie; adaptorové proteiny signální transdukční; Risk; Rare variants; Genetic Variation; SQSTM1/p62; Female; riziko; lidé středního věku; Middle Aged